Longitudinal changes in cutting kinematics in young female athletes across puberty - Chia, L.; Hewett, T.; Ford, K.; Myer, G.; McKay, M.; Sullivan, J.; Evangelos, P. (British Journal of Sports Medicine, 2021)
Background Young female athletes involved in high-speed cutting and change-of-direction sports are particularly susceptible to anterior cruciate ligament (ACL) injuries. Little is known if maturational changes in cutting technique contribute to the increased injury risk.